2021
DOI: 10.1021/acs.iecr.1c00732
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature Formaldehyde Oxidation on the Pt/Na-ZSM-5 Catalyst: Tuning Adsorption Capacity and the Pt Chemical State

Abstract: Catalytic oxidation is believed to be the most efficient method for indoor formaldehyde purification. Herein, we reported that the Pt/Na-ZSM-5 catalyst with low Pt loading (0.16 wt %) prepared by depositing Pt on Na+ ion-exchanged ZSM-5 could completely oxidize 300 ppm formaldehyde in 2.5 vol % H2O at 32 °C and maintain its activity during the 62 h-long stability test. Multiple characterizations revealed that the presence of Na species significantly enhanced formaldehyde adsorption ability and made Pt species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…When Na is added, a peak appears near 1072.4 eV, which is assigned to the formation of an −O−Na linkage that stabilizes the Pt atoms, and the peak intensity gradually increases with the increase in Na content. 59 Although the Na content of Pt@Sil-1-6Na is higher than that of Pt@Sil-1-4Na, the peak intensities of both Pt@Sil-1-6Na and Pt@Sil-1-4Na are the same. More quantitative data for the surface content and bulk content of Pt and Na based on the XPS and ICP are listed in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…When Na is added, a peak appears near 1072.4 eV, which is assigned to the formation of an −O−Na linkage that stabilizes the Pt atoms, and the peak intensity gradually increases with the increase in Na content. 59 Although the Na content of Pt@Sil-1-6Na is higher than that of Pt@Sil-1-4Na, the peak intensities of both Pt@Sil-1-6Na and Pt@Sil-1-4Na are the same. More quantitative data for the surface content and bulk content of Pt and Na based on the XPS and ICP are listed in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…There is no signal for Pt/Sil-1 and Pt@Sil-1 catalysts, indicating that there is no Na on the catalyst surface. When Na is added, a peak appears near 1072.4 eV, which is assigned to the formation of an −O–Na linkage that stabilizes the Pt atoms, and the peak intensity gradually increases with the increase in Na content . Although the Na content of Pt@Sil-1-6Na is higher than that of Pt@Sil-1-4Na, the peak intensities of both Pt@Sil-1-6Na and Pt@Sil-1-4Na are the same.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, PtO x is reduced at 100 ℃-300 ℃, but the reduction of Pt 2+ and Pt 4+ coordinated with -(-O-Si≡) y of ZSM-5 requires about 450 ℃ and 550 ℃ [41,42]. However, the reduction peak of pure ZSM-5 did not appear in the H 2 -TPR process.…”
Section: H 2 -Tprmentioning
confidence: 96%
“…The alkali metals can be electronic or structural promoters, improving the activity of catalysts markedly . Previous literature studies have reported that alkali metal doping generates noble metal–alkali–O x –(OH) y species, which could be active sites for water-gas shift reactions. ,, In addition, alkali metal addition induces a decrease in the particle size of noble metal particles as well as increases the dispersion of the noble metals and surface OH groups, resulting in a promotion effect on HCHO oxidation. To our knowledge, researchers have mainly focused on the interaction between noble metals and alkali metals, but the interaction between alkali metals and the supports has not been fully explored. Therefore, it is necessary to study how alkali metals interact with supports and further affected noble metal anchoring so that the catalytic promotion mechanism of alkali metals can be understood.…”
Section: Introductionmentioning
confidence: 99%